[Discussion of Cognitive Aspects of Annual Reports: Field Independence/ Dependence]: A Reply - Lusk, Edward J. (Journal of Accounting Research, 1973)
Edward J. Lusk, [Discussion of Cognitive Aspects of Annual Reports: Field Independence/ Dependence]: A Reply, Journal of Accounting Research, Vol. 11, Empirical Research in Accounting: Selected Studies 1973 (1973), pp. 215-224